Is oral dydrogesterone equivalent to vaginal micronized progesterone for luteal phase support in women receiving oocyte donation? - Margaux Lorillon; Geoffroy Robin; Laura Keller; Emeline Cailliau; Clémence Delcourt; Virginie Simon; Christine Decanter; Sophie Catteau-Jonard (Reproductive Biology and Endocrinology)
Abstract Research question To determine whether the use of oral dydrogesterone (DYD) in luteal phase support (LPS) during an artificial cycle provides equivalent clinical and ongoing pregnancy, delivery and miscarriage rates as micronized vaginal progesterone (MVP) in oocyte donation recipients. Design This was a retrospective observational study of prospectively collected data from the assisted reproductive technology (ART) Department of Lille University Hospital from July 2018 to July 2022. All recipients underwent endometrial preparation by an artificial cycle. Luteal phase support (LPS) was provided by weekly intramuscular progesterone (IM) (500 mg/2 ml) and either DYD (40 mg/day) or MVP (800 mg/day) for 12 weeks if the pregnancy test was positive. The primary endpoint was the clinical pregnancy rate. Results Our study analysed 372 oocyte donation cycles with embryo transfer: 162 embryo transfers with DYD + IM progesterone and 210 embryo transfers with MVP + IM progesterone. After adjustment for confounding factors, our two groups were comparable in terms of clinical pregnancy rates, with 36.7% in the MVP group versus 30.3% in the DYD group (p = 0.55); ongoing pregnancy rates (29,1% versus 25.3%, p = 0.95); miscarriage rates (7.6% versus 4.9%, p = 0.35); and live birth rates (26.7% versus 25.3%, p = 0.86). Conclusion Oral dydrogesterone seems to be a good alternative to vaginal micronized progesterone for LPS treatment during an artificial cycle, especially in combination with a weekly injection of intramuscular progesterone in the course of oocyte donation.